Epigenetic regulation of RELN and GAD1 in the frontal cortex (FC) of autism spectrum disorder (ASD) subjects - Zhubi, Adrian; Chen, Ying; Guidotti, Alessandro; Grayson, Dennis R. (International journal of developmental neuroscience, 2017)
•The RELN and GAD1 mRNA levels were reduced in ASD PFC.•TET 1, 2, and 3 mRNAs were increased in ASD PFC.•There was increased DNMT1 and MECP2 promoter binding.•5mC and 5hmC levels in the promoters do not account for the increased binding. These data and a study on the cerebella from the same ASD cohort are discussed. Both Reelin (RELN) and glutamate decarboxylase 67 (GAD1) have been implicated in the pathophysiology of Autism Spectrum Disorders (ASD). We have previously shown that both mRNAs are reduced in the cerebella (CB) of ASD subjects through a mechanism that involves increases in the amounts of MECP2 binding to the corresponding promoters. In the current study, we examined the expression of RELN, GAD1, GAD2, and several other mRNAs implicated in this disorder in the frontal cortices (FC) of ASD and CON subjects. We also focused on the role that epigenetic processes play in the regulation of these genes in ASD brain. Our goal is to better understand the molecular basis for the down-regulation of genes expressed in GABAergic neurons in ASD brains. We measured mRNA levels corresponding to selected GABAergic genes using qRT-PCR in RNA isolated from both ASD and CON groups. We determined the extent of binding of MECP2 and DNMT1 repressor proteins by chromatin immunoprecipitation (ChIP) assays. The amount of 5-methylcytosine (5mC) and 5-hydroxymethylcytosine (5hmC) present in the promoters of the target genes was quantified by methyl DNA immunoprecipitation (MeDIP) and hydroxyl MeDIP (hMeDIP). We detected significant reductions in the mRNAs associated with RELN and GAD1 and significant increases in mRNAs encoding the Ten-eleven Translocation (TET) enzymes 1, 2, and 3. We also detected increased MECP2 and DNMT1 binding to the corresponding promoter regions of GAD1, RELN, and GAD2. Interestingly, there were decreased amounts of 5mC at both promoters and little change in 5hmC content in these same DNA fragments. Our data demonstrate that RELN, GAD1, and several other genes selectively expressed in GABAergic neurons, are down-regulated in post-mortem ASD FC. In addition, we observed increased DNMT1 and MECP2 binding at the corresponding promoters of these genes. The finding of increased MECP2 binding to the RELN, GAD1 and GAD2 promoters, with reduced amounts of 5mC and unchanged amounts of 5hmC present in these regions, suggests the possibility that DNMT1 interacts with and alters MECP2 binding properties to selected promoters. Comparisons between data obtained from the FC with CB studies showed some common themes between brain regions which are discussed.